Monticalia speciosa (Senecioneae, Compositae), a noteworthy new species from Ecuador - Calvo, Joel; Romoleroux, Katya (Phytotaxa, 2019)
A new species of Monticalia with minute, ciliate leaves, radiate capitula, and eight involucral bracts is described from the northern Andes of Ecuador. It is a striking shrub that has been oddly overlooked until now. It grows in the highlands of Papallacta, a very humid páramo characterized by harboring many lagoons. Photographs of living plants of the new species and a related taxon are provided.